Decreased The Anxiety Scale of Hemodialysis Patients With The Spiritual Emotional Freedom Technique (SEFT) and The Autogenic Relaxation - Liza Fitri Lina; Hazaroh Eldis Sabriyanti; Andry Sartika (lppm Universitas Muhammadiyah Semarang, 2019)
Problems that can be rendered by hemodialysis include anxiety, relationships in marriage, and disobedience in diet and medicine, limitations in lifestyle and threat of death. The purpose of this study was to find out the effectiveness comparison between the Spiritual Emotional Freedom Technique (SEFT) with autogenic relaxation to decrease the anxiety scale of hemodialysis patients. The research design employed Quasy Experiment Without Control Group Design. The results of independent t-test analysis in the Emotional Spiritual intervention group Freedom Technique (SEFT) obtained results p = 0,000, in the Autogenic Relaxation intervention group the results were p = 0,000. The results of the independent t-test analysis showed that p = 0.184. The study indicates that there was no difference between the Spiritual Emotional Freedom Technique (SEFT) and Autogenic Relaxation on decreasing the anxiety scale of hemodialysis patients. It is looked forward that the Hospital can enforce independent interventions such as Spiritual Emotional Freedom Technique (SEFT) and Autogenic Relaxation to degrade the anxiety scale of hemodialysis patients.